96 = 6(k + 4)
k =
17 answers
16
s + 18/7
= 4
s =
= 4
s =
-2
are you sure
I made a mistake in my previous response. Let me correct it:
s + 18/7 = 4
Subtract 18/7 from both sides:
s = 4 - 18/7
s = 28/7 - 18/7
s = 10/7
So, s = 10/7 or approximately 1.43.
s + 18/7 = 4
Subtract 18/7 from both sides:
s = 4 - 18/7
s = 28/7 - 18/7
s = 10/7
So, s = 10/7 or approximately 1.43.
4 =
b/7− 3
b/7− 3
To solve for b, we need to isolate b on one side of the equation:
4 = b/7 - 3
Add 3 to both sides:
4 + 3 = b/7
7 = b/7
Multiply both sides by 7 to solve for b:
7 * 7 = b
49 = b
Therefore, b = 49.
4 = b/7 - 3
Add 3 to both sides:
4 + 3 = b/7
7 = b/7
Multiply both sides by 7 to solve for b:
7 * 7 = b
49 = b
Therefore, b = 49.
k/9+ 32
= 39
k =
= 39
k =
To solve for k, we can follow these steps:
k/9 + 32 = 39
Subtract 32 from both sides:
k/9 = 7
Multiply both sides by 9 to isolate k:
k = 7 * 9
k = 63
Therefore, k = 63.
k/9 + 32 = 39
Subtract 32 from both sides:
k/9 = 7
Multiply both sides by 9 to isolate k:
k = 7 * 9
k = 63
Therefore, k = 63.
m − 53/9
= 3
m =
= 3
m =
To solve for m, we can follow these steps:
m - 53/9 = 3
To get rid of the fraction 53/9, first bring 3 to a fraction with a common denominator of 9:
3 = 27/9
m - 53/9 = 27/9
Now combine the fractions on one side:
m - 53/9 = 27/9
Now, we add 53/9 to both sides:
m = 27/9 + 53/9
m = 80/9
Therefore, m = 80/9.
m - 53/9 = 3
To get rid of the fraction 53/9, first bring 3 to a fraction with a common denominator of 9:
3 = 27/9
m - 53/9 = 27/9
Now combine the fractions on one side:
m - 53/9 = 27/9
Now, we add 53/9 to both sides:
m = 27/9 + 53/9
m = 80/9
Therefore, m = 80/9.
how
Apologies for the confusion in my previous response. Let's correctly solve the equation for m:
m - 53/9 = 3
Add 53/9 to both sides:
m = 3 + 53/9
m = 27/9 + 53/9
m = 80/9
Therefore, m = 80/9 or approximately 8.89.
m - 53/9 = 3
Add 53/9 to both sides:
m = 3 + 53/9
m = 27/9 + 53/9
m = 80/9
Therefore, m = 80/9 or approximately 8.89.
no
Let's go through the problem again:
m - 53/9 = 3
Add 53/9 to both sides to isolate m:
m = 3 + 53/9
m = 27/9 + 53/9
m = 80/9
Therefore, m = 80/9.
m - 53/9 = 3
Add 53/9 to both sides to isolate m:
m = 3 + 53/9
m = 27/9 + 53/9
m = 80/9
Therefore, m = 80/9.
3(n + 16) = 87
n =
n =
To solve for n, we can follow these steps:
3(n + 16) = 87
First, distribute the 3 on the left side:
3n + 48 = 87
Subtract 48 from both sides:
3n = 87 - 48
3n = 39
Divide by 3 to isolate n:
n = 39 / 3
n = 13
Therefore, n = 13.
3(n + 16) = 87
First, distribute the 3 on the left side:
3n + 48 = 87
Subtract 48 from both sides:
3n = 87 - 48
3n = 39
Divide by 3 to isolate n:
n = 39 / 3
n = 13
Therefore, n = 13.